Ameloblastic fibrosarcoma: clinicopathological and molecular analysis of seven cases highlighting frequent BRAF and occasional NRAS mutations. Issue 6 (16th April 2020) - Agaimy, Abbas; Skalova, Alena; Franchi, Alessandro; Alshagroud, Rana; Gill, Anthony J; Stoehr, Robert; Baumhoer, Daniel; Bauer, Sebastian
Abstract : Aims: Ameloblastic fibrosarcoma (AFS) is an aggressive odontogenic neoplasm featuring malignant mesenchymal stroma in addition to an ameloblastic epithelial component, and is hence considered to be the malignant counterpart of ameloblastic fibroma (AF). AFS is exceedingly rare, with <110 cases having been reported so far. Although BRAF mutations are recognised driver mutations in ameloblastoma, the molecular pathogenesis of AFS remains elusive. Methods and results: We herein describe seven AFSs that were analysed, for the first time, for mutations in the BRAF – NRAS pathway. The patients were four females and three males aged 23–57 years (median, 26 years). Three tumours developed after one or multiple recurrences of AF (4–20 years after initial diagnosis), two showed transition from AF‐like bland areas, and two developed de novo . All patients were treated with surgery; adjuvant chemotherapy was given to one patient. At the last follow‐up, five patients were alive and well (19–344 months). The remainder were lost to follow‐up. Histological examination showed variable sarcomatous overgrowth with varying degrees of atypia and increased mitotic activity. The epithelial component varied greatly according to the degree of sarcomatous overgrowth. Molecular testing revealed BRAF V600E mutations in five cases and NRAS p.Gln61Lys mutation in one case. One tumour was wild‐type. Conclusion: To our knowledge, this is the first study on BRAF / NRAS mutations in AFS. Given the activity of RAF and MEK inhibitors across different cancers harbouring V600E mutations, our data strongly suggest that all AFS cases should be genetically tested, and that targeted treatment approaches for this extremely rare sarcoma subtype should be clinically investigated.